IMF Survey, Volume 35, Issue 10. (IMF Survey; IMF Survey ;, 2006)
De Rato on global imbalances; Committee to study IMF finances; IMF management change; Country briefs: Maldives, Israel; Emerging soverign debt markets; Euro area imbalances; Preference erosion; Import protection; Effects of IMF program; ECOSOC meeting.